The Effect of Lean Manufacturing Practices and Supply Chain Integration on Sustainable Performance: The Mediating Role of Green Supply Chain Management (A Study on the Use of Used Oil) - Muhammad Nur Muharmy; Sutarman; Ratnasari Siregar Khairani (PT. Publikasiku Academic Solution, 2026)
The coal mining sector in Indonesia faces increasing pressure to balance operational productivity with global sustainability standards, encompassing economic, social, and environmental dimensions. One critical issue requiring strategic intervention is the management of Hazardous and Toxic Waste (B3), particularly the accumulation of used oil generated from heavy equipment maintenance activities. In response to this challenge, PT Bukit Asam Tbk (PTBA) has implemented a circular economy program through its On-Site Plant and Waste Oil Preparation Plant (OSP and WOPP), which converts used oil into a diesel fuel substitute for explosives. However, the success of this initiative depends largely on the organization’s ability to manage internal efficiency and supply chain connectivity to achieve optimal sustainable performance. This study aimed to examine the effects of Lean Manufacturing Practices and Supply Chain Integration on Sustainable Performance, with Green Supply Chain Management (GSCM) as a mediating variable. Lean Manufacturing Practices were implemented to minimize waste in operational processes, while Supply Chain Integration strengthened coordination between internal functions and strategic partners. This synergy was expected to enhance GSCM implementation, increase economic value, minimize environmental impacts, and demonstrate how GSCM mediation connects operational practices with long-term corporate sustainability objectives. A quantitative approach was employed by distributing questionnaires to stakeholders involved in the used oil management supply chain at PTBA. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) to examine the significance of relationships among the research variables. The findings are expected to provide a reference for the mining industry in developing integrated waste management strategies while contributing empirical evidence to the literature on green supply chain management in developing economies.